Making correctional health care smarter. - Allison, Tom L.; Clark, John H. (Corrections Today, 2001)
The introduction of computerized patient record technology into health-care systems will improve knowledge available to leaders and decision makers. Health care has struggled with the development and enhancement of computerized patient records and electronic medication administration records over the past 20 years. As the inmate population keeps on changing, the tasks of tracking medical records, administering medication and scheduling clinic visits can be difficult and time-consuming, particularly using a nonautomated record-keeping system. A computer-based health-care system, the Jail Health Information System, is being implemented throughout the 20,000-bed Los Angeles County Jail, and this will allow doctors, nurses, and clinicians to better perform patient care tasks.